Effect of wood vinegar and rice husk biochar on soil properties and growth performances of immature kenaf (Hibiscus cannabinus) planted on BRIS soil (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Beach ridges interspersed with swales (BRIS) soil is identified as one of Malaysia's problematic soil since this type of soil contains a plethora portion of sand texture that contributes to water and nutrient leaching causes infertile soil. A polybag trial was conducted to evaluate the effects of wood vinegar and rice husk biochar on soil properties and growth performances of immature kenaf. The plant was arranged in a completely randomised design with four treatments and three replications. The factors taken for the experiment were four different media compositions, i.e., T1(control), T2(BRIS soil amended with wood vinegar, WV), T3(BRIS soil amended with rice husk biochar, RHB) and T4(BRIS soil amended with wood vinegar and rice husk biochar, WV+RHB). Rice husk biochar and a combination of wood vinegar with rice husk biochar significantly improved soil properties in terms of soil moisture content, organic matter, water retention and soil porosity, as well as significantly increased the kenaf stem diameter. However, there was no significant difference in plant height, number of leaves, leaves area and chlorophyll content on different treatments medium. In conclusion, the application of rice husk biochar and wood vinegar in this study enhanced BRIS soil properties and showed a positive effect on the growth of immature kenaf.
Keywords: Biochar; BRIS Soil; Kenaf; Growth Performance; Wood Vinegar